A Polish adaptation of leadership scale for sports - A questionnaire examining coaching behavior - Walach-Bista, Z. (Human Movement, 2013)
Purpose. The main purpose of this study was the development of a Polish version of the scale developed by P. Chelladurai and S. Saleh for examining coaching behavior (the Leadership Scale for Sports; LSS). Methods. The Polish version was constructed in two stages. In the first stage, the psychometric equivalence of the Polish translation was estimated by providing a Polish/English version of the questionnaire to a bilingual sample. Following verification of the psychometric properties of the experimental version and the adding of additional items to the scale, a second stage of analysis was performed using additional samples to assess the reliability and validity of the new scale. In total, 560 university physical education students, 180 athletes, and 75 coaches were recruited to participate in the study. The final version was deemed a reliable and valid reproduction of the LSS, consisting of 40 items representing five dimensions measuring coaching behavior. Results. Measures of reliability (internal consistency using Cronbach`s alpha and test-retest reliability) as well as validity (exploratory factory analysis with principal component analysis) of the final version of the Polish adaptation of the Leadership Scale for Sports were found to be satisfactory. It was determined that the Polish adaptation of the LSS is characterized by good psychometric properties and can be widely used in the sports environment. Conclusions. The Polish adaptation of the LSS reflects the five-factor structure of the original scale, closely reproducing the dimensions of training and instruction, democratic behavior, autocratic behavior, social support, and positive feedback. It can be used both for the measurement athletes` preferences for coaching behavior and for assessing coaching behavior as observed by athletes.